Draining Over Blocking: Nano‐Composite Janus Separators for Mitigating Internal Shorting of Lithium Batteries. Issue 12 (11th February 2020) - Gonzalez, Matthew S.; Yan, Qizhang; Holoubek, John; Wu, Zhaohui; Zhou, Hongyao; Patterson, Nicholas; Petrova, Victoria; Liu, Haodong; Liu, Ping
Abstract: Catastrophic battery failure due to internal short is extremely difficult to detect and mitigate. In order to enable the next‐generation lithium‐metal batteries, a "fail safe" mechanism for internal short is highly desirable. Here, a novel separator design and approach is introduced to mitigate the effects of an internal short circuit by limiting the self‐discharge current to prevent cell temperature rise. A nano‐composite Janus separator—with a fully electronically insulating side contacting the anode and a partially electronically conductive (PEC) coating with tunable conductivity contacting the cathode—is implemented to intercept dendrites, control internal short circuit resistance, and slowly drain cell capacity. Galvanostatic cycling experiments demonstrate Li‐metal batteries with the Janus separator perform normally before shorting, which then results in a gradual increase of internal self‐discharge over >25 cycles due to PEC‐mitigated shorting. This is contrasted by a sudden voltage drop and complete failure seen with a single layer separator. Potentiostatic charging abuse tests of Li‐metal pouch cells result in dendrites completely penetrating the single‐layer separator causing high short circuit current and large cell temperature increase; conversely, negligible current and temperature rise occurs with the Janus separator where post mortem electron microscopy shows the PEC layer successfully intercepts dendrites. Abstract : Internal short circuit events in Li‐ion batteries and Li‐metal batteries can result in rapid self‐discharge leading to dangerous thermal runaway and catastrophic cell failure. This novel bilayer Janus separator design represents a new approach to preventing catastrophic internal short circuit, not by blocking the short circuit but rather by intercepting it to slowly drain battery capacity.